IN THE LIGHT OF ASEAN ECONOMIC COMMUNITY: THE PROTECTION OF MINING RESOURCES IN INDONESIA, DECENTRALIZATION SYSTEM AND THE ROLE OF GOVERNMENT POLICY - Wahyuni, Indria (UI Scholars Hub, 2016)
In 2015 Indonesia will facing Asean Economic Community (AEC) which open thekey for free trade among the Asean Countries. In response to this phase, Indonesia need to be prepared in many fields, one of them is the miningfield. As a country rich of natural resources, mining field managementurgently need to have attention. With AEC there will be potential investment and flow of human resources, Indonesia must prepare themselveswithsufficient human resources, infrastructure and legal policy. Recent, thereare significant problems in mining field that comes from regulations,miningthat should be able to support and escalates the Indonesian prosperiety loosetheir function due to corruption. The ground of such condition is the overlapping regulations in the field, no harmonized regulation that ended tono accountable mining system in Indonesia. Different natural resources hasdifferent regulation that often does not correlate each other. Mining activities at least observed by three ministries namely Ministry of Energy and Mineral Resources of Republic Indonesia, the Ministry of Forestry, National Land Agency, it is become a big problem while issuing regulations related to mining. With implementation of decentralization system, local government also has authority in terms of managing mining activity in their area. The paper, furthermore, highlihted aspects that need to improve intermsofuildinggoodmining system in Indonesia. This paper will ended with discussion and solution for aspects that the Local Government can take part and what kind of policy that they can made in order to protect the environment in their area, as well as to create sustainability mining for futher generation.